The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jaridenv.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus biogeochemistry across a precipitation gradient in grasslands of central North America

Abstract: a b s t r a c t Soil P transformations and distribution studies under water limited conditions that characterize many grasslands may provide further insight into the importance of abiotic and biotic P controls within grassdominated ecosystems. We assessed transformations between P pools across four sites spanning the shortgrass steppe, mixed grass prairie, and tallgrass prairie along a 400-mm precipitation gradient across the central Great Plains. Pedon total elemental and constituent mass balance analyses ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
4
27
0
1
Order By: Relevance
“…The results on P fractionation are based on the extents of weathering and similar effects of weathering can be achieved by all possible combinations of factors. Many workers have found that P fractionation patterns depends on the intensity of weathering which they assign to the function of different local factors, such as topography (Smeck, 1985), geology and topography (Agbenin and Tiessen, 1994;Dieter et al, 2010) and rainfall and vegetation (Chadwick et al, 2003;Ippolito et al, 2010). Therefore, the P fractionation trends found in this study are in general applicable to all kind of soil sequences having similar extents of weathering.…”
Section: Discussionsupporting
confidence: 52%
“…The results on P fractionation are based on the extents of weathering and similar effects of weathering can be achieved by all possible combinations of factors. Many workers have found that P fractionation patterns depends on the intensity of weathering which they assign to the function of different local factors, such as topography (Smeck, 1985), geology and topography (Agbenin and Tiessen, 1994;Dieter et al, 2010) and rainfall and vegetation (Chadwick et al, 2003;Ippolito et al, 2010). Therefore, the P fractionation trends found in this study are in general applicable to all kind of soil sequences having similar extents of weathering.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, mineralized P underneath groves may be immobilized not only by biological uptake but also via the formation of calcium phosphates in basic subsurface soils, as suggested in other studies in dryland environments (Carreira et al, 2006;Ippolito et al, 2010). Mineralized C and N, ultimately, leave the soil profile via gas emissions (e.g., CO 2 , N 2 , and nitrogen oxides), plant uptake (e.g., NO À 3 and NH þ 4 ), and leaching.…”
Section: Soil C-n-p Imbalance In Surface Soils Following Woody Encrmentioning
confidence: 79%
“…Compared to herbaceous species, trees/ shrubs in dryland areas typically have enlarged rhizospheres in both horizontal and vertical dimensions (Jackson et al, 1996;Schenk & Jackson, 2002), resulting in amplified SOM input throughout the soil profile following woody encroachment. Meanwhile, accumulations of soil organic C, N, and P are also determined by abiotic factors, such as physicochemical binding between SOM and soil minerals (i.e., clay and silt particles; Schmidt et al, 2011;Six, Conant, Paul, & Paustian, 2002) that affect microbial decomposition of SOM and favor the accumulation of soil C, N, and P. In addition, soil pH has been shown to affect the chemical form and solubility of inorganic P, and alkaline soils in dryland areas would generally favor the precipitation of dissolved inorganic P leached from surface soils as calcium phosphates (Carreira, Vinegla, & Lajtha, 2006;Ippolito et al, 2010;Schlesinger & Bernhardt, 2013). While there is a rich literature reporting the effects of these biotic/abiotic factors on net changes in soil C, N, and/or P following woody encroachment, individually or in combination, no studies have simultaneously tested the relative importance of these factors on all three elements.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and intensity of dry-rewetting cycles can influence nutrient availability and microbial function (Chowdhury et al 2011). Long droughts can trap nutrients in SOM or on carbonate (Ippolito et al 2010) and have created nutrient limitations at both wetter (Tiemann and Billings 2011) and drier (Yahdjian and Sala 2010) sites. Meanwhile frequent rain events increase nutrient availability in the soil (Fierer andSchimel 2003, Butterly et al 2009).…”
Section: Discussionmentioning
confidence: 99%